The specificity of public stigma: A comparison of suicide and depression-related stigma. (October 2017) - Sheehan, Lindsay; Dubke, Rachel; Corrigan, Patrick W.
Abstract: Each year, approximately 1.3 million Americans survive a suicide attempt. While stigma has been reported by suicide attempt survivors, limited research has examined how suicide stigma may differ from the stigma of mental illness. U.S. adults (n = 440) completed an online survey in which they were randomly assigned to one of four vignettes. Vignettes depicted a target individual with either past depression, past suicide attempt, death by suicide, or no information on suicide or mental illness (control). Participants completed a general measure of stigma, a suicide-specific stigma measure, and were surveyed on the recovery potential of individuals with mental illness and suicide attempt. While the general stigma measure failed to distinguish between groups, significant differences on the suicide stigma scale (SSAS-44) emerged between participants assigned in the depression and suicide conditions, especially for stereotype and prejudice subscales. Across conditions, participants believed that recovery was more realistic for someone described as having a mental illness than it was for someone described as having attempted suicide. These findings suggest that individuals who have attempted suicide are subject to differential stigma content from those with depression. Implications are discussed for combating stigma for suicide attempt survivors. Highlights: Public stigma of suicide differs from public stigma of mental illness, especially for stereotype and prejudice subscales. Belief in recovery was lower for a person with history of suicide attempt than for a person with a mental illness. Individuals who attempt suicide may experience stigma related to both suicide and mental illness.